Role of Indian Tourism in Economic Growth of Country - Akarsh Tiwari; Aditya Bisen (Journal of Social Responsibility, Tourism and Hospitality, 2023)
This research paper explores the significant role played by Indian tourism in fostering economic growth within the country. It analyzes the various dimensions of tourism and its impact on the national economy, considering factors such as foreign exchange earnings, employment generation, infrastructure development, and regional economic disparities. The findings indicate that tourism has emerged as a crucial sector for India’s economic progress, presenting opportunities for further development and policy interventions to maximize its potential.